Removal of Ammoniacal Nitrogen from Aqueous Medium Through Ultrafiltration Assisted by Cation-Exchange-Water-Soluble Polymers - Tapiero-Martinez, y (Elsevier Ltd, 2025)
Swine wastewater is recognized as a significant environmental concern due to its high concentrations of ammonium nitrogen (N-NH4+), which typically range from 400 to 4500 mg L−1. To address this issue, the application of polymer-enhanced ultrafiltration (PEUF) has been proposed as a method for removing N-NH4+ from aqueous media. This study utilized sodium poly(acrylate) (PNaA) and potassium poly(3-sulphopropyl acrylate) (PKSPA) as adsorbents for NH4+ removal. Key operating parameters, including pH, polymer dosage, initial NH4+ concentration, and applied pressure, were analyzed. With PNaA, the presence of divalent cations did not negatively affect the retention performance, which remained at 72 %, nor did it impact the permeate flux. In contrast, when PKSPA was used, the strong competition between NH4+, Ca2+, and Mg2+ ions for the functional groups resulted in a decrease in NH4+ retention, dropping from 71 % to 59 %, along with a lower permeate flux. The enrichment method identified a maximum N-NH4+ removal capacity of 685.7 mg N g−1 PKSPA when treating simulated wastewater from the swine industry. The observed decrease in permeate flux was attributed to the formation of macromolecular aggregates, which blocked the pores of the ultrafiltration membrane. Thus, PEUF emerges as a promising approach for the removal of N-NH4+ from swine wastewater. © 2025 Elsevier Ltd